Presence of microporosity in Miocene carbonate platform, Central Luconia, offshore Sarawak, Malaysia - Janjuhah, H.T. (Springer Verlag, 2018)
The Luconia Provinceâoffshore Sarawakâis a key hydrocarbon province in Malaysia. However, the gas reservoirs in Central Luconia pose unique problems and challenges as they have partially water-filled microporosity that overprint wireline logs. Microporosity in Central Luconia occurs throughout the Miocene carbonates and is a crucial element that influences fluid flow properties and ultimately the recovery of hydrocarbons. Quantification of macroporosity was achieved using petrographic analysis of thin sections and the FESEM images. The point counting technique was used to estimate the amount of macroporosity from the thin section, which was then subtracted from the total porosity to derive microporosity. The qualitative investigation of the Miocene carbonates indicates the presence of three different types of microporosity namely grain-based microporosity, matrix-based microporosity, and cement-based microporosity. Quantification of microporosity showed that the microporosity varies from sample to sample, ranging from 10 to 60 of the total measured porosity. The depositional texture, mineralogy, and microtexture control this microporosity variation including its abundance and type. The microporosity in Central Luconia is diagenetically controlled based on four major diagenetic mechanisms namely (1) mechanical process/endolithic grains/marine diagenesis; (2) leaching/meteoric diagenesis; (3) cementation/shallow diagenesis; and (4) deeper diagenesis environment. Â© 2018, Saudi Society for Geosciences.